STUDI HADIS DENGAN PENDEKATAN SOSIOLOGIS: Paradigma Living-Hadis - Ja’far Assagaf (Holistic al-Hadis, 2015)
As a paragon who is followed by Muslims, the Prophet Muhammad’s hadiths serve as one of the main sources for Islamic tenets as a universal religion for all mankind. Meanwhile, the prophet was also a man who lived in a society with certain cultures, traditions, and geographical elements which differ, to some extent, from those of Muslims all over the world.Sociological approaches to the life of the Prophet, thus, become necessary in order to realize his guidance by contextual understanding to the gist of hadiths. Sociological approaches can be done by combiningdifferent perspectives of Sociology, such as Sociology of religion, Sociology of Language, Sociology of Culture, and so on, with Sociological theories which are widely well-known in either Islamic world or the West. In order not to be detached from the spirit of Islam, the analysis from the Sociological perspectives should be combined with hadith’s sciences (‘ûlûm al-ḥadîth) covering the isnâd and the matn. The significance of such kind of approach can be seen in its possibilities to reveal –to mention some of them- why the transmitters and collectors of hadith have the similar names and why one hadith seems to contradict the other. Some sub-disciplines of hadith sciences which have been combined with sociological approaches (including names, tittles, country of origins of the transmitters, as well as the contradictive and strange hadith) can prove significance of Sociological approaches to the study of hadith.